To drain or not to drain: the association between residual intraperitoneal gas and post-laparoscopic shoulder pain for laparoscopic cholecystectomy - Shun-Chin Yang (Nature Portfolio, 2021)
Abstract Residual intra-peritoneal gas may be associated with post-laparoscopic shoulder pain (PLSP), which is a frequently and disturbance compliant after surgery. Herein, we aimed to examine whether expiring residual gas via a surgical drain reduces the frequency and intensity of PLSP in the first day after laparoscopic cholecystectomy. 448 participants were enrolled in this prospective cohort study. The incidence and severity of PLSP after surgery were recorded. Of these, the cumulative incidence of PLSP in the drain group was lower particularly at the 12th postoperative hour (18.3% vs. 27.6%; P = 0.022), 24th postoperative hour (28.8% vs. 38.1%; P = 0.039), and throughout the first postoperative day (P = 0.035). The drain group had less severe PLSP (crude Odds ratio, 0.66; P = .036). After adjustment using inverse probability of treatment weighting, the drain group also had a significant lower PLSP incidence (adjusted hazard ratio = 0.61, P < 0.001), and less severe PLSP (adjusted odds ratio = 0.56, P < 0.001). In conclusion, the maneuver about passive force to expel residual gas, surgical drain use, contributes to reduce the incidence and severity of PLSP, suggesting that to minimize residual gas at the end of surgery is useful to attenuate PLSP.